2016
DOI: 10.1039/c6mt00058d
|View full text |Cite
|
Sign up to set email alerts
|

The emerging role of lysosomes in copper homeostasis

Abstract: The lysosomal system operates as a focal point where a number of important physiological processes such as endocytosis, autophagy and nutrient sensing converge. One of the key functions of lysosomes consists of regulating the metabolism/homeostasis of metals. Metal-containing components are carried to the lysosome through incoming membrane flows, while numerous transporters allow metal ions to move across the lysosome membrane. These properties enable lysosomes to direct metal fluxes to the sites where metal i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
65
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 76 publications
(71 citation statements)
references
References 90 publications
6
65
0
Order By: Relevance
“…In vitro experiments have shown that excessive addition of copper to the cell culture medium can induce autophagy, and the autophagy here is recognized as a cellular defense mechanism that can reduce cell death [100]. The elevation of copper has been observed in lysosomes, the organelles involved in autophagy [101]. In the redox cycle of metal ions, elevation of copper promotes autophagy and apoptosis of glioma cells by reactive oxygen species and JNK activation [102,103].…”
Section: Coppermentioning
confidence: 99%
“…In vitro experiments have shown that excessive addition of copper to the cell culture medium can induce autophagy, and the autophagy here is recognized as a cellular defense mechanism that can reduce cell death [100]. The elevation of copper has been observed in lysosomes, the organelles involved in autophagy [101]. In the redox cycle of metal ions, elevation of copper promotes autophagy and apoptosis of glioma cells by reactive oxygen species and JNK activation [102,103].…”
Section: Coppermentioning
confidence: 99%
“…ATP7B is normally expressed in liver hepatocytes and operates in maintaining copper homeostasis in the body. In response to Cu overload, ATP7B moves from the Golgi to endo-lysosomal structures where it sequesters excess Cu and promotes its excretion into the bile [10,11]. Loss-of-function mutations prevent ATP7B from sequestering Cu and its removal from cells leading to severe Cu toxicosis, which is known as Wilson disease [12].…”
Section: Introductionmentioning
confidence: 99%
“…Low expression of CTR1 has been associated with poor clinical outcome in NSCLC patients who had received platinum-based chemotherapy (Kim et al, 2014). Interestingly, the copper transporting ATPases, ATP7A and ATP7B, have been suggested to chelate and/or promote the cellular efflux of platinum-based drugs (Dolgova et al, 2009;Gupta and Lutsenko, 2009;Katano et al, 2004;Polishchuk and Polishchuk, 2016;Safaei and Howell, 2005). Studies have revealed a correlation between elevated ATP7B expression and reduced effectiveness of cisplatin chemotherapy in cancer patients (Miyashita et al, 2003;Nakayama et al, 2004).…”
Section: Discussionmentioning
confidence: 99%